Blockchain and ethereum smart contract solution development : Dapp Programming with solidity - Zhang, Weijia; Anand, Tej (Apress L.P., 2022)
Build decentralized applications with smart contract programming. Following the curriculum from an active blockchain course taught by the author at the McCombs School of Business at the University of Texas, this book fills the gaps for you from learning about basic cryptocurrency uses of blockchain to understanding smart contracts and dapps. You'll first start by understanding the basics of blockchain technology. Take a business point of view to discover general concepts about blockchains and dapps or "decentralized apps" built off of smart contracts. Next, learn about the token economy, how to design tokens, and relevant client technologies, such as web3, metamask, and UI/UX design. Then, install a blockchain node yourself. With a basic understanding of blockchain applications and business uses, you'll move further into hands-on development. There are ten modules for hands-on smart contract programming covered to build your own decentralized applications. Several team projects built end-to-end from concept to deployment to operation are also provided. Using these models and your own original work, you'll build a smart contract development environment, practice Solidity programming, compile source code, perform security reviews, and deploy bytecode to blockchains. The breakthrough in blockchain technology has empowered novel ecosystems and applications in the areas of Decentralized Finance (DeFi), Central Bank Digital Currency (CBDC), Non-Fungible Tokens (NFT), Decentralized Autonomous Organization (DAO), and more. Blockchain and Ethereum Smart Contract Solution Development will prepare you to create fantastic applications using Ethereum's smart contracts and solid concepts of decentralized programming! What You'll Learn Become familiar with Blockchain technology, both in theory and in practice Understand architectural components of blockchain and the underlying computer science Implement blockchain smart contract solutions using both public and enterprise Ethereum blockchains Who This Book Is For IT professionals and mid-level managers interested in smart contract development. Blockchain Consultants who want to have a handbook of smart contract development methodologies. And enterprise technologiests helping companies through the transformation to blockchain technologies